Artesunate Combined With Metformin Ameliorate on Diabetes-Induced Xerostomia by Mitigating Superior Salivatory Nucleus and Salivary Glands Injury in Type 2 Diabetic Rats via the PI3K/AKT Pathway - Zhang, Siqin; Li, Jiarui; Nong, Xiaolin; Zhan, Yuxiang; Xu, Jiazhi; Zhao, Danni; Ma, Chubin; Wang, Yuchen; Li, Yixing; Li, Zhan; Li, Jiaquan (Frontiers in Pharmacology, 2021)
Polydipsia and xerostomia are the most common complications that seriously affect oral health in patients with diabetes. However, to date, there is no effective treatment for diabetic xerostomia. Recent studies have reported that artesunate (ART) and metformin (Met) improve salivary gland (SG) hypofunction in murine Sjögren’s syndrome. Therefore, aim of this study was to investigate the effect and underlying mechanism of artesunate (ART) alone and in combination with metformin (Met) on hyposalivation in type 2 diabetes mellitus (T2DM) rats. T2DM rats were induced using a high-fat diet and streptozotocin. SPF male Sprague–Dawley rats were divided into the following five groups: normal control group, untreated diabetic group, ART-treated diabetic group (50 mg/kg), Met-treated diabetic group (150 mg/kg), and ART/Met co-treated diabetic group (50 mg/kg ART and 150 mg/kg Met). ART and Met were intragastrically administered daily for 4 weeks. The general conditions, diabetes parameters and serum lipids were evaluated after drug treatment. Furthermore, we observed changes in the central superior salivatory nucleus (SSN) and SG, and changes in the AQP5 expression, parasympathetic innervation (AChE and BDNF expression), and PI3K/AKT pathway- (p-AKT, and p-PI3K), apoptosis- (Bax, Bcl-2, and Caspase3), and autophagy- (LC3 and P62) related markers expression in T2DM rats after treatment. Our results showed that ART or Met alone and ART/Met combination attenuated a range of diabetic symptoms, including weight loss, urine volume increase, water consumption increase, hyperglycemia, insulin resistance, glucose intolerance and dyslipidemia. More importantly, we found that these three treatments, especially ART/Met combination, mitigated hyposalivation in the T2DM rats via improving the central SSN and SGs damage in hyperglycemia. Our data also indicated that ART/Met attenuated SG damage though regulating the PI3K/Akt pathway to inhibit apoptosis and autophagy of SGs in the T2DM rats. Moreover, ART/Met preserved parasympathetic innervation (AChE and BDNF expression) in SGs to alleviate diabetes-induced hyposalivation likely through rescuing central SSN damage. Taken together, these findings might provide a novel rationale and treatment strategy for future treatment of diabetes-induced xerostomia in the clinic.